2022
DOI: 10.3390/ma15134723
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Mn-Doped SrTiO3/Carbon Fiber with Oxygen Vacancy for Enhanced Photocatalytic Hydrogen Evolution

Abstract: With carbon fiber, it is difficult to load semiconductor photocatalysts and easy to shed off thanks to its smooth surface and few active groups, which has always been a problem in the synthesis of photocatalysts. In the study, SrTiO3 nanoparticles were loaded onto the Tencel fibers using the solvothermal method, and then the Tencel fibers were carbonized at a high temperature under the condition of inert gas to form carbon fibers, thus SrTiO3@CF photocatalytic composite materials with solid core shell structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
(54 reference statements)
2
9
0
Order By: Relevance
“…The CF/SrTiO 3 composite fiber, featuring a core-shell heterojunction structure, was prepared using the method outlined in previous studies [10,11]. Generally, this involves coating a SrTiO 3 nanolayer onto Tencel fibers via the solvothermal method at 180 • C for 7 h, followed by carbonizing the fibers at 800 • C for 2 h under nitrogen to form CF/SrTiO 3 .…”
Section: Preparation Of Cf/srtio 3 /In 2 O 3 Composite Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CF/SrTiO 3 composite fiber, featuring a core-shell heterojunction structure, was prepared using the method outlined in previous studies [10,11]. Generally, this involves coating a SrTiO 3 nanolayer onto Tencel fibers via the solvothermal method at 180 • C for 7 h, followed by carbonizing the fibers at 800 • C for 2 h under nitrogen to form CF/SrTiO 3 .…”
Section: Preparation Of Cf/srtio 3 /In 2 O 3 Composite Materialsmentioning
confidence: 99%
“…In addition, its excellent conductivity enhances the rapid transfer of photogenerated electrons, improving photocatalytic performance. In previous studies, we successfully synthesized CF/SrTiO 3 composite fiber materials and demonstrated that doping with Mn or incorporating CdS enhances light absorption and photogenerated electron transport, thereby improving the photocatalytic performance and facilitating the recyclability of the composite [10,11]. In this work, CF/SrTiO 3 composite fiber material was employed as a substrate for the initial deposition of In seeds.…”
Section: Introductionmentioning
confidence: 96%
“…Among the many photocatalytic materials, strontium titanate (SrTiO 3 ) has attracted attention because of its good structural stability, corrosion resistance, and appropriate conduction band and valence band energy levels 18,19 . However, SrTiO 3 ‐based photocatalysts still have some shortcomings, such as a high recombination rate of photogenerated electron–hole pairs, 20 poor utilization rate of the light source, and unfavorable recycling 21,22 . Therefore, significant efforts have been dedicated to develop more effective methods to resolve these issues.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 However, SrTiO 3 -based photocatalysts still have some shortcomings, such as a high recombination rate of photogenerated electron-hole pairs, 20 poor utilization rate of the light source, and unfavorable recycling. 21,22 Therefore, significant efforts have been dedicated to develop more effective methods to resolve these issues. A modifying agent can be added to the SrTiO 3 structure to improve its properties as a photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have endeavored to tackle the challenges of low light absorption capacity and inadequate utilization of photo-generated charges in SrTiO 3 photocatalysts. For instance, scientists have successfully integrated Pt, Pd, Ni, Fe, Mn, and Au into the lattice or surface of SrTiO 3 , resulting in notable enhancements in light absorption and photocatalytic activity [13][14][15][16][17][18][19][20][21][22][23]. Yue and co-workers synthesized SrTiO 3 nanofibers (NFs) via a facile electrospinning method, followed by the deposition of Mo 2 C on the surface of SrTiO 3 NFs through ultrasonic and thermal treatment under an Ar atmosphere to optimize the photocatalytic H 2 generation rate [24].…”
Section: Introductionmentioning
confidence: 99%